Aliadas en Cadena: training in feminine entrepreneurship as a strategy to leave poverty (Mayéutica Revista Científica de Humanidades y Artes, 2021)
Poverty has become an economic problem that has exceeded the response capacity of governments in third world countries. The consequences of this have impacts in the short, medium and long term, not only in terms of the formulation of public policies, but also in the quality of life of the people who suffer the attacks of it. It is estimated that 70% of the people living in these conditions of poverty are women, which forces both the public and private sectors to work together and generate feasible strategies to reduce this alarming figure. Entrepreneurship training specifically aimed at the female sector, assumed by Aliadas en Cadena A.C., is the objective of the research. A descriptive methodology, field and analysis of twelve years of activity of the organization in Venezuela is applied, in which entrepreneurial training has been provided to a total of 984 women from vulnerable sectors in the cities of Caracas, Barquisimeto, Valencia and Maracaibo The results observed focus on the importance that women give to their empowerment and selfesteem, elements that will translate into values for their children, society as well as generate a productive activity for their own economic sustenance.
Keywords: Women entrepreneurship; training; empowerment; Aliadas en Cadena